Ba3(PO4)2 Photocatalyst for Efficient Photocatalytic Application - Yassine Naciri; Ayoub Ahdour; Elhassan Benhsina; Mahmoud Adel Hamza; Asmae Bouziani; Abdelghani Hsini; Bahcine Bakiz; Jose Antonio Navío; Mohamed Nawfal Ghazzal (Global Challenges, 2024)
Abstract Barium phosphate (Ba3(PO4)2) is a class of material that has attracted significant attention thanks to its chemical stability and versatility. However, the use of Ba3(PO4)2 as a photocatalyst is scarcely reported, and its use as a photocatalyst has yet to be reported. Herein, Ba3(PO4)2 nanoflakes synthesis is optimized using sol‐gel and hydrothermal methods. The as‐prepared Ba3(PO4)2 powders are investigated using physicochemical characterizations, including XRD, SEM, EDX, FTIR, DRS, J–t, LSV, Mott‐Schottky, and EIS. In addition, DFT calculations are performed to investigate the band structure. The oxidation capability of the photocatalysts is investigated depending on the synthesis method using rhodamine B (RhB) as a pollutant model. Both Ba3(PO4)2 samples prepared by the sol‐gel and hydrothermal methods display high RhB photodegradation of 79% and 68%, respectively. The Ba3(PO4)2 obtained using the sol‐gel process exhibits much higher stability under light excitation after four regeneration cycles. The photocatalytic oxidation mechanism is proposed based on the active species trapping experiments where O2•‒ is the most reactive species. The finding shows the promising potential of Ba3(PO4)2 photocatalysts and opens the door for further investigation and application in various photocatalytic applications.